2021
DOI: 10.26434/chemrxiv-2021-bz00c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing Electrochemical Carbon Dioxide Reduction by Polymer-Encapsulated Cobalt Phthalocyanine through Incorporation of Graphite Powder

Abstract: Cobalt phthalocyanine (CoPc) has been extensively studied as a catalyst for the electrochemical reduction of CO2 to value-added products. Previous studies have shown that CoPc is a competent and efficient catalyst when immobilized onto carbon-based electrodes using a polymer binder, especially when immobilized with a graphitic carbon powder support to increase charge transport. In this study, we systematically explore the influence of incorporating graphite powder (GP) into a polymer-encapsulated CoPc on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Catalyst loading was determined as previously described . After centrifugation, the graphitic pellet was digested by the addition of 15 mL of TraceMetal Grade 1 M HNO 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalyst loading was determined as previously described . After centrifugation, the graphitic pellet was digested by the addition of 15 mL of TraceMetal Grade 1 M HNO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Porphyrins and phthalocyanines have been studied as molecular electrocatalysts for the CO 2 RR, with cobalt phthalocyanine (CoPc) being a particularly well-studied catalyst due to its unique electron configuration and favorable binding energy to CO 2 . CoPc easily adsorbs to carbon electrode surfaces and has been an important model system to study the mechanism of the CO 2 RR , as well as one of the rare molecular catalysts able to reduce CO 2 to methanol under specific reaction conditions. , Our particular interest in CoPc has focused on improving the selectivity of CoPc-catalyzed CO 2 RR over the competing HER by encapsulating the parent complex within coordinating polymers to control the local microenvironment. Our group and others , have shown that encapsulating CoPc within poly­(4-vinylpyridine) (P4VP) results in increased reaction activity and selectivity for the CO 2 RR over the HER, leading to an increase in Faradaic efficiency for CO production from 60% for CoPc to >90% for CoPc-P4VP and a four-fold increase in turnover frequency for CO production. ,, …”
Section: Introductionmentioning
confidence: 99%